2019
DOI: 10.18632/oncotarget.27172
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan activated-metabolism phenotype (HAMP) in pancreatic ductal adenocarcinoma

Abstract: Background: The aggressiveness of pancreatic ductal adenocarcinoma (PDAC) is enhanced by its interactions with stromal extracellular matrix, notably with hyaluronan (HA). Our previous studies have demonstrated increased expression of genes involved in HA synthesis and degradation in PDAC, suggesting the presence of an autocrine mechanism which accelerates the production of low-molecular-weight HA. Results: A subset of PDAC (20% of cell lines and 25% of tissues) showed overexpression of multiple genes encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
(40 reference statements)
2
13
0
Order By: Relevance
“…Our previous studies identified a novel phenotype, HAMP (hyaluronan-activated metabolism phenotype), characterized by activation of multiple HA metabolism cascades, in PDAC 34 . HAMP was defined as the increased expression of multiple HA metabolism genes, including KIAA1199.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies identified a novel phenotype, HAMP (hyaluronan-activated metabolism phenotype), characterized by activation of multiple HA metabolism cascades, in PDAC 34 . HAMP was defined as the increased expression of multiple HA metabolism genes, including KIAA1199.…”
Section: Discussionmentioning
confidence: 99%
“…(31) For example, an enhanced expression of KIAA1199 in the nucleus, as well as cytoplasm, was discovered in colon cancer cells and also the plasma of cancer patients, and had significant correlation with patients' clinical characteristics. (32,33) Kudo et al (34) also found the upregulation of KIAA1199 in pancreatic cancer tissues which was associated with patients' survival outcome. It suggested that KIAA1199 could be regarded as a biomarker for cancer prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…51 This was reinforced by a recent study showing significantly higher HA levels in primary PDACs compared with sites of metastases 59 ; among various metastatic sites, HA was expressed most abundantly in liver metastases. The higher levels of HA in primary tumors in comparison with metastatic sites, in conjunction with the association of high CEMIP protein and poor survival of stage I/II PDAC patients, 27 as well as similar HA abundance in PDAC patients with stage II (95% HA-positive, n = 47) and stage III (86% HA-positive, 15,18,22,25 Not upregulated Kohi et al 25 found high quantity of HYAL1 (measured by ELISA) was significantly associated with more advanced stage. Cheng et al 20 found low expression of HYAL1 (IHC) to be significantly associated with poor survival.…”
Section: Ha In Tumors Of Pdac Patientsmentioning
confidence: 94%